Transformation of Multicultural Education Based on Islamic Moderation at PTKIN: Synergy of Curriculum, Leadership, and Empowerment - lailiyah, ifa (Maliki Interdisciplinary Journal, 2025)
This article examines the transformation of multicultural education based on Islamic moderation within State Islamic Higher Education Institutions (PTKIN). The rise of radicalism and the decline of academic culture present urgent challenges that must be addressed systematically. Multicultural education that is interconnected and integrative can serve as a solution through the strengthening of religious curricula, deliberative leadership, student empowerment, and the role of libraries as centers of scientific communication. The article concludes that there is a need for synergy between a curriculum grounded in Islamic moderation values, academic management reform, and a participatory leadership model to build an inclusive, productive, and tolerant PTKIN ecosystem